Optimizing Lecturer Performance Through Online Learning Competence and Job Satisfaction in the Post-Pandemic Era - Nelvi Nurul Huda; Elisabet Siahaan (Management Institute Faculty of Economics Universitas Andalas, 2022)
Changes in the online learning system in the post-covid-19 pandemic in universities are very important to study because universities had started reorganizing their activities before the covid-19 pandemic struck. The online learning system is still being implemented even though the frequency of use is not one hundred percent anymore like during the covid-19 pandemic. Learning activities have returned to normal, so lecturers are required to develop their ideas by sharing online learning methods to shape the character of competent and competitive graduates. Lecturer performance is also supported by job satisfaction, which is a problem related to the emotions of a lecturer in carrying out his duties. Not many studies examine the impact of online learning competence and job satisfaction on lecturer performance in the post-pandemic era. The population in this study were all permanent lecturers of STAI Al-Ishlahiyah Binjai, totaling 74 people, where the entire population was sampled. The data analysis technique used path analysis and Sobel Test to test the significance level of the intervening variable. The results of the study prove that online learning competence has a positive and significant effect on lecturer job satisfaction, online learning competence has a positive and significant effect on lecturer performance, job satisfaction has a positive and significant effect on lecturer performance.